Hearing in Time: Psychological Aspects of Musical Meter - London, Justin (New York Oxford University Press, 2012)
This book develops a theory of musical meter based on psychological research in temporal perception, cognition, and motor behavior. Meter is regarded as a kind of entrainment, a synchronization of attention and actions to the rhythms of the environment. Drawing on research on the ability to make durational discriminations and categorizations at various tempos, the speed limits for meter are given: the inter-onset interval for metric elements must be greater than 100ms (10 per second) and less than 1.5-2.00 seconds. Care is taken to distinguish rhythms or patterns of duration from meters, the listener/performer's complex patterns of expectation and attention. It is thus shown that metric behaviors are highly tempo-dependent. Ambiguities may arise when a rhythmic pattern may be regarded under more than one meter, and conflicts may arise when a pattern of durations contradicts the ongoing meter. The theoretical core of the book is its development of a set of metric well-formedness constraints, which limit the temporal range and organization of patterns of metric entrainment. A consideration of the rhythmic practices of various non-western cultures, including some African and Indian music, leads to an additional well-formedness constraint, that of maximal evenness. This allows for meters that involve uneven (i.e., non-isochronous) beats. The book concludes with the many meters hypothesis, which proposes that a large number of expressively timed temporal templates are acquired, which are readily used when listening in familiar musical contexts.
Keywords: Meter; Tempo; Rhythm; Music psychology; Musical analysis